2015
DOI: 10.3892/ol.2015.3811
|View full text |Cite
|
Sign up to set email alerts
|

Measuring body composition using the bioelectrical impedance method can predict the outcomes of gemcitabine-based chemotherapy in patients with pancreatobiliary tract cancer

Abstract: Abstract. In order to examine the effect on body composition of anticancer drug treatments, the body composition rate in patients being treated with gemcitabine (GEM)-based chemotherapy was measured over time on an outpatient basis with a simple body composition monitor using the bioelectrical impedance (BI) method. The results revealed a significant reduction in the body fat rate (P=0.01) over the course of treatment in patients with pancreatobiliary tract cancer who became unable to continue GEM-based chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The application of bioimpedance has long been investigated in medical areas to identify human tissues or detect invisible lesions, and its accuracy is relatively high. [ 7 10 ] As to larger samples, we found that several studies published recently reported that BIS can detect breast cancer surgery related arm lymphedema at an earlier stage. In these studies, researchers put 2 measurement electrodes at 10 cm intervals along the dorsal surface of the patient's arm at locations of 10, 20, 30, and 40 cm from the ulnar styloid.…”
Section: Introductionmentioning
confidence: 80%
“…The application of bioimpedance has long been investigated in medical areas to identify human tissues or detect invisible lesions, and its accuracy is relatively high. [ 7 10 ] As to larger samples, we found that several studies published recently reported that BIS can detect breast cancer surgery related arm lymphedema at an earlier stage. In these studies, researchers put 2 measurement electrodes at 10 cm intervals along the dorsal surface of the patient's arm at locations of 10, 20, 30, and 40 cm from the ulnar styloid.…”
Section: Introductionmentioning
confidence: 80%
“…It is considered that these disorders of various metabolic/nutrition pathways accompanied with cancer progression lead to the decrease of ghrelin production or the increase of interleukin-6 (IL-6) production, which causes loss of appetite, malnutrition, and cancer cachexia. We have previously studied the body composition of advanced pancreato-biliary cancer patients and have reported the importance of maintaining body fat in order to continue cancer chemotherapy [4].…”
Section: Introductionmentioning
confidence: 99%